61 Right ventricular function in patient with heart failure with reduced ejection fraction and sacubitril/valsartan treatment. (8th December 2021) - Mazzeo, Pietro; Fortunato, Martino; Croella, Francesca; Alfieri, Simona; Fanizzi, Angela Ilaria; Furore, Andrea; Ferrara, Salvatore; Tricarico, Lucia; Correale, Michele; Iacoviello, Massimo; Di Biase, Matteo; Brunetti, Natale D
Abstract: Aims: Observational studies have demonstrated that treatment with sacubitril/valsartan may improve left ventricular (LV) systolic and diastolic function in subjects with reduced LV ejection fraction (LVEF) in real-world studies. Subjects with heart failure and reduced EF (HFrEF), however, are also characterized by an impaired right ventricular (RV) function. We therefore aimed to evaluate whether also RV function may improve after S/V therapy and possible predictors of RV improvement could be identified at echocardiography and tissue Doppler imaging. Methods: Fifty consecutive patients (67 ± 8 years, LVEF 28 ± 6%, male 86%) with chronic HFrEF and NYHA Classes II–III were followed up for 6 months after therapy with S/V. LV&RV function was assessed at baseline and after 6 months of therapy. Results: After 6-month therapy with S/V a significant improvement was shown in the following echocardiography parameters assessing RV function: PAsP (31 ± 11 vs. 35 ± 10 mmHg, P < 0.001), TAPSE (19 ± 3 vs. 18 ± 3 mm, P < 0.001), RV FAC (38 ± 7 vs. 34 ± 6 mm, P < 0.001), RV S' (12 ± 2 vs. 10 ± 2 cm/sec, P < 0.001), RV-FW-LS (−20 ± 5 vs. −18 ± 5%, P < 0.001), RV-4Ch-LS (−16 ± 5 vs. −14 ± 5%, P < 0.001). At multivariable analysis improvement in RV-FW-LS was associated to baseline levels of RV S' ( r 0.75, P < 0.01) and RAV ( r –0.32, P < 0.05). Conclusions: In a real-world scenario, 6-month therapy with S/V was associated with an improved RV function in HFrEF. RV function improvement may be predicted by assessing baseline RV S' and right atrial volume values.